Vertical coupling and transport in high-latitude ionosphere - Pokhotelov, Dimitry; Günzkofer, Florian Ludwig; Stober, Gunter; Fernandez Gomez, Isabel; Borries, C. (2022)
Various plasma anomalies appear at auroral latitudes, extending across the polar cap as a tongue of ionisation (TOI) and polar patches (PPs). Mechanisms responsible for horizontal and vertical plasma transport include the forcing from above (solar irradiance and geomagnetic activity) and from below (atmospheric waves and tides). The forcing mechanisms balance each other in lower thermosphere, forming the ionospheric transition region. At higher altitudes (the F layer), plasma irregularities can be transported for hours, while in the E layer and below the irregularities recombine within seconds. Incoherent (ISR) and coherent scatter radars can observe vertical coupling and dynamics at various horizontal scales, providing a tool for analysing the transition region. Modelling with GCMs provides a basis for mitigating/forecasting the space weather. Vertical coupling and transport will be addressed in connection to the drifting polar cap anomalies (TOI and PPs). Examples of the vertical coupling and transport with the EISCAT ISR will show relative contributions of the forcing from above and below. Examples of plasma irregularities seen by GNSS receiver networks and SAR radars will be also shown.